2017
DOI: 10.1175/mwr-d-16-0316.1
|View full text |Cite
|
Sign up to set email alerts
|

The Relative Importance of Stratiform and Convective Rainfall in Rapidly Intensifying Tropical Cyclones

Abstract: Using 16-yr Tropical Rainfall Measuring Mission (TRMM) Precipitation Radar (PR) observations, rainfall properties in the inner-core region of tropical cyclones (TCs) and the relative importance of stratiform and convective precipitation are examined with respect to the evolution of rapid intensification (RI) events. The onset of RI follows a significant increase in the occurrence and azimuthal coverage of stratiform rainfall in all shear-relative quadrants, especially upshear left. The importance of the increa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
50
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 62 publications
(63 citation statements)
references
References 41 publications
12
50
1
Order By: Relevance
“…While there are some previous microphysical observations in TC eyewalls, the number of samples in major hurricanes are very limited due to the rarity of the phenomena and difficulty in sampling. The low-level convergence and upward motion mostly occur in the downshear direction, where abundant hydrometeors are generated and then advected downwind to the left of the shear vector, where the reflectivity maximum is frequently observed (Black et al, 2002;DeHart et al, 2014;Foerster et al, 2014;Hence & Houze, 2011;Reasor et al, 2013;Tao et al, 2017). Of particular interest to the current study is the influence of VWS on Harvey's eyewall structure prior to landfall, which introduced a strong asymmetry in the observed polarimetric variables.…”
Section: Introductionmentioning
confidence: 92%
“…While there are some previous microphysical observations in TC eyewalls, the number of samples in major hurricanes are very limited due to the rarity of the phenomena and difficulty in sampling. The low-level convergence and upward motion mostly occur in the downshear direction, where abundant hydrometeors are generated and then advected downwind to the left of the shear vector, where the reflectivity maximum is frequently observed (Black et al, 2002;DeHart et al, 2014;Foerster et al, 2014;Hence & Houze, 2011;Reasor et al, 2013;Tao et al, 2017). Of particular interest to the current study is the influence of VWS on Harvey's eyewall structure prior to landfall, which introduced a strong asymmetry in the observed polarimetric variables.…”
Section: Introductionmentioning
confidence: 92%
“…Jiang and Ramirez (2013) found the following necessary conditions for RI in the inner core: total raining area >3,000 km 2 , total volumetric rain >5,000 mm · hr · km 2 , maximum near-surface radar reflectivity >40 dBZ, maximum 20-dBZ (40-dBZ) echo height >8 (4) km, minimum 85-GHz polarization-corrected brightness temperature <235 K, and minimum 10.8-mm brightness temperature <220 K. Using airborne Doppler radar data, Rogers et al (2013) found that intensifying TCs have a larger number of convective bursts located inside the radius of maximum wind. Tao et al (2017) showed that the onset of RI follows a significant increase in the occurrence and azimuthal coverage of stratiform rainfall in all shear-relative quadrants, especially upshear left, which are related to the moistening/humidification of the inner core, particularly in the upshear quadrants. Tao et al (2017) showed that the onset of RI follows a significant increase in the occurrence and azimuthal coverage of stratiform rainfall in all shear-relative quadrants, especially upshear left, which are related to the moistening/humidification of the inner core, particularly in the upshear quadrants.…”
Section: Introductionmentioning
confidence: 97%
“…Convective structure within the inner core of TCs also plays an important role in RI (Alvey et al, 2015;Harnos & Nesbitt, 2011;Fischer et al, 2018;Harnos & Nesbitt, 2016;Jiang, 2012;Jiang & Ramirez, 2013;Kieper & Jiang, 2012;Rogers et al, 2013;Rogers et al, 2015;Tao & Jiang, 2015;Tao et al, 2017;Zagrodnik & Jiang, 2014). Using long-term Tropical Rainfall Measurement Mission satellite data, Harnos and Nesbitt (2011) found that TCs undergoing RI have 85-GHz signatures depicting a moderately intense convective ring surrounding the storm center associated with low wind shear.…”
Section: Introductionmentioning
confidence: 99%
“…Using the two dimensional composites of V for wavenumber-0 and -1, ratios of wavenumber-1 amplitude to the total low-wavenumber amplitude (V 1 /V 0+1 ) are calculated and mean radial profiles of this ratio are computed for each shear relative quadrant (USL, DSL, DSR, USR). Following the description in Alvey et al (2015) and Tao et al (2017), a low wavenumber asymmetry index (AIDX) is then determined in the following manner:…”
Section: Relative Contribution Of Wind Shear On Tc Surface Wind Strucmentioning
confidence: 99%
“…Figure 3.4. In panels (a-d), TC intensity dependent radial profiles of wavenumber-1 asymmetry ratio (V 1 /V 0+1 ) are provided in the form of the four shear-relative quadrant absolute differences that define an asymmetry index (Alvey et al 2015;Tao et al 2017). 'DS' and 'US' refer to down-shear and up-shear and the additional 'L' or 'R' indicates right or left, respectively.…”
Section: Relative Contribution Of Wind Shear On Tc Surface Wind Strucmentioning
confidence: 99%